PENGEMBANGAN BAHAN AJAR KETERAMPILAN MENULIS NARASI MENGGUNAKAN STRATEGI THINK, TALK, WRITE (TTW) DI KELAS V SEKOLAH DASAR - Monica Theresia; Nurbaiti . (Jurnal Education and Development, 2020)
The purpose of developing this teaching material is to produce valid, practical and effective narrative writing teaching materials. The study used the Plomp development model which consisted of three stages, namely: preliminary research, the design stage (prototyping phase) and the assessment phase. Based on the results of the validity test, the RPP validation was 87.8% (very valid), and teaching materials 88.2% (very valid). The practicality test results obtained by the implementation of RPP 88.82% very practical category, 92.2% teacher response assessment very practical category, one to one stage assessment 87.5% (very practical), assessment at the small group stage 82.5% (very practical), the assessment at the field test stage is 81.6% (very practical). The results of the effectiveness test were obtained from the activities of students 88.3% (very high), the results of the assessment of the narrative writing process were 84.5% (very high) and the average assessment of the results of narrative essays was 82.2% (very good). Based on these results, it can be concluded that narrative writing teaching materials use the Think Talk Write (TTW) strategy that was developed to be valid, practical and effective in teaching narrative writing in grade V Elementary School.